E(x,y,z) = kq·< f(x),f(y),f(z) >
¬E(x,y,z) = kq·< g(y,z),g(z,x),g(x,y) >
div[ E(x,y,z) ] = d_{x}[f(x)]+d_{y}[f(y)]+d_{z}[f(z)]
d_{xyz}^{3}[ Flux[ E(x,y,z) ] ] = d_{x}[f(x)]+d_{y}[f(y)]+d_{z}[f(z)]
div[ ¬E(x,y,z) ] = 0
d_{xyz}^{3}[ Flux[ ¬E(x,y,z) ] ] = 0
rot[ E(x,y,z) ] = kq·< x·( f(y)+(-1)·f(z) ),y·( f(z)+(-1)·f(x) ),z·( f(x)+(-1)·f(y) ) >
rot[ ¬E(x,y,z) ] = kq·< x·( g(z,x)+(-1)·g(x,y) ),y·( g(x,y)+(-1)·g(y,z) ),z·( g(y,z)+(-1)·g(z,x) ) >
flux[ rot[ E(x,y,z) ] ] = 0
flux[ rot[ ¬E(x,y,z) ] ] = ...
... x·( int[ g(y,z) ] d[y]·z+(-1)·int[ g(y,z) ] d[z]·y )+...
... y·( int[ g(z,x) ] d[z]·x+(-1)·int[ g(z,x) ] d[x]·z )+...
... z·( int[ g(x,y) ] d[x]·y+(-1)·int[ g(x,y) ] d[y]·x )
d_{t}[ E(x,y,z) ] = ...
... kq·< d_{x}[f(x)]·d_{t}[x], d_{y}[f(y)]·d_{t}[y],d_{z}[f(z)]·d_{t}[z] >
J(x,y,z) = d_{t}[ E(x,y,z) ]+rot[ E(x,y,z) ]
d_{t}[ ¬E(x,y,z) ] = ...
... kq· ...
... < ...
... int[ d_{yz}^{2}[g(y,z)]·d_{t}[y]·d_{t}[z] ] d[t], ...
... int[ d_{zx}^{2}[g(z,x)]·d_{t}[z]·d_{t}[x] ] d[t], ...
... int[ d_{xy}^{2}[g(x,y)]·d_{t}[x]·d_{t}[y] ] d[t] ...
... >
¬J(x,y,z) = d_{t}[ ¬E(x,y,z) ]+rot[ ¬E(x,y,z) ]
E(x,y,z) = ...
... kq·< f(x),f(y),f(z) >
¬E(x,y,z) = ...
... (1/2)·kq·< f(y)+f(z),f(z)+f(x),f(x)+f(y) >
E(x,y,z) = ...
... kq·< e^{f(x)},e^{f(y)},e^{f(z)} >
¬E(x,y,z) = ...
... kq·< e^{( f(y)+f(z) )},e^{( f(z)+f(x) )},e^{( f(x)+f(y) )} >
No hay comentarios:
Publicar un comentario